Women chief technology officers in community colleges - Wiggins, Monica D. (Kansas State University, 2021)
This study used a qualitative phenomenological method to investigate the experiences of women chief technology officers in community colleges and their experiences that led to attainment of leadership roles in technology. Throughout the history of the United States, citizens have witnessed gender inequality in the workforce. The gender inequality faced by women in the workforce, specifically technology fields, is a concern that promotes an absence of diversity, inclusion, female role models, and varied perspectives; which further supports inequality in salaries and leadership attainment. Without a balance, barriers that women face in the workforce will continue to prevail. The purpose of this study was to describe the experiences of women chief technology officers in community colleges. The study sought to identify the lessons learned during their journeys to gain a deeper understanding of their experiences that led to attainment of leadership roles in technology. In addition, the study sought to discover factors that supported persistence through potential social and systemic barriers and deterrents. The intent of the study was to discover and define their experiences in the workforce (specifically the technology sector), education, and organizational structures. This study goes beyond the barriers and deterrents that current literature highlights about bias and stereotype threats, and informs the technology field by providing practical methods through the use of positive mindsets that project an invincible determination to persist in technology. Those with high self–efficacy levels may view barriers as tasks to master and conquer (Zimmerman, Schunk, & DiBenedetto, 2015). The women of this study viewed barriers as temporary nuisances that they either had to go through, over, or around to master or conquer, but never did they view barriers as permanent obstacles keeping them from reaching their goals. Positive mindsets allowed the women to reverse negative barriers into opportunities. The women took intimidating settings, such as meetings filled with men, and used such situations as platforms to promote women in technology among the men. When the women were tasked with completing degrading work with no extra pay, they accepted the tasks and completed them as if they were high priority tasks, and volunteered to complete additional projects that others refused, thus displaying unintentional leadership qualities to executive management. In addition, during leadership development, the women used common daily practices, such as staying organized, documenting processes, and showing respect to all levels. These are simple methods that women aspiring technology can apply immediately in the workplace. This study discovered that, although the participants understood the negative aspects of being in the technology field, the passion they have for helping people through the use of technology, the community college, and growing women in technology to leverage equity in the future of technology for women, far outweighed any deterrents or barriers to persistence. A deeper understanding of the lessons learned from the women chief technology officers in community colleges in this study contributes to knowledge of how more women may persist and attain technology leadership success through the recommendation of possessing positive mindsets.
Keywords: Women in technology; Women leaders; Technology; Community colleges; Leadership; Gender bias